Pengaruh Penggunaan Multimedia Interaktif dengan Adobe Captivate Terhadap Hasil Belajar Kanji (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2014)
Interactive multimedia is the combination of different types of media presentation and teaching methods which uses some media such as visual, audio, video etc. The purpose of this research is to find out the difference between the result of studies by using an interactive multimedia by adobe captivate and without interactive multimedia as teaching tool for students of second year at Faculty of Japanese Language in College Foreign Language of JIA in Bekasi. By using this media, the students can be more focus and active in learning process.